1H NMR-based metabolomics study of breast meat from Pekin and Linwu duck of different ages and relation to meat quality. (July 2020) - Wang, Xiangrong; Jiang, Guitao; Kebreab, Ermias; Li, Jinghui; Feng, Xiaoyu; Li, Chuang; Zhang, Xu; Huang, Xuan; Fang, Chengkun; Fang, Rejun; Dai, Qiuzhong
Graphical abstract: Highlights: Slaughter age exerted a greater effect on duck meat quality than breed. Difference of metabolite profiles in duck breast meat at 72d was greater than 42d. Six metabolites were strongly related to the quality traits of duck breast meat. Abstract: This study investigated the effects of breed and age on meat quality, and metabolite profiles of duck breast meat, and the relationship between changes in metabolite profiles and the meat quality. The meat quality and 1 H nuclear magnetic resonance (NMR)-based metabolomics of breast meat from Pekin and Linwu ducks at 2 different ages (42 and 72d) was analyzed. The results showed that age exerted a greater effect on the observed meat quality traits of breast meat than breed, and its interaction (breed × age) effect on pH values and yellowness (b*) of duck breast meat was significant. Total of 32 metabolites were detected in breast meat of Pekin and Linwu duck. The difference of metabolite profiles in breast meat between Pekin and Linwu duck at 72 d was greater than that at 42 d, while the effects of age on metabolites of duck meat from both breeds were similar. Anserine, aspartate, and carnosine were the most relevant metabolites of duck breast meat quality, and nicotinamide in duck breast meat was negatively correlated with cooking loss. ﻿ These results provide an overall perspective for bridging the gap between the breed and age on duck meat quality and metabolome, and improve the understanding of the relationship between metabolites and duck meat quality.